Going with the Grain of Cognition: Applying Insights from Psychology to Build Support for Childhood Vaccination - Rossen, Isabel; Hurlstone, Mark J.; Lawrence, Carmen (Frontiers in Psychology, 2016)
Childhood vaccination is widely considered to be one of the most successful public health interventions. Yet, the effective delivery of vaccination depends upon public willingness to vaccinate. Recently, many countries have faced problems with vaccine hesitancy, where a growing number of parents perceive vaccination to be unsafe or unnecessary, leading some to delay or refuse vaccines for their children. Effective intervention strategies for countering this problem are currently sorely lacking, however. Here, we propose that this may be because existing strategies are grounded more in intuition than insights from psychology. Consequently, such strategies are sometimes at variance with basic psychological principles and assumptions. By going against the grain of cognition, such strategies potentially run the risk of undermining persuasive efforts to reduce vaccine hesitancy. We demonstrate this by drawing on key insights from cognitive and social psychology to show how various known features of human psychology can lead many intuitively appealing intervention strategies to backfire, yielding unintended and undesirable repercussions. We conclude with a summary of potential avenues of investigation that may be more effective in addressing vaccine hesitancy. Our key message is that intervention strategies must be crafted that go with the grain of cognition by incorporating key insights from the psychological sciences.